Development and Content Validity of the Participation and Sensory Environment Questionnaire. (3rd April 2018) - Pfeiffer, Beth; Coster, Wendy; Tucker, Carole; Piller, Aimee
ABSTRACT: Qualitative methodology was used to develop items for a questionnaire designed to examine the perspectives of parents regarding the impact of the sensory environment on participation for children aged 3 to 5 who have autism spectrum disorders. A total of 34 parents/caregivers of children with autism spectrum disorders and 8 experts in autism spectrum disorders and/or measurement completed qualitative interviews for concept, content review, and cognitive interviewing. The result was a pool of 35 items for home/community domains for 3 scales. The outcome of this study was the development and content validation of the Participation and Sensory Environment Questionnaire.